An empirical study of 'green' workplace behaviours: ability, motivation and opportunity. (27th April 2017) - Rayner, Julie; Morgan, Damian
Abstract : Green human resource management contributes to an understanding of the role of human resource management (HRM) towards sustainability and environmental outcomes. This paper assesses employees' environmental knowledge as well as self‐perceptions of ability, motivation and opportunity (AMO) to practise green behaviours by operationalising the AMO framework towards a pro‐environmental agenda. The study draws on a survey sample of 394 employees from five organisations in regional Australia. Key findings show that pro‐environmental AMO are positively associated with green behaviours and that these are more prevalent at home than in the workplace. Further, line managers moderate the relationship between pro‐environmental AMO and green behaviour although not the relationship between environmental knowledge and green behaviour. Such benchmark measurement informs HRM policies, practices and interventions and contributes to environmental management. Key points: Promoting a green culture and behaviours that eliminate or reduce harm to the environment have been shown to benefit organisations in a multitude of ways. Pro‐environmental AMO predicts green behaviours and these behaviours are more prevalent at home than in the workplace. Line managers moderate the relationship between pro‐environmental AMO and green behaviour although not the relationship between environmental knowledge and green behaviour. Benchmark measurement using such an AMO tool can inform future HRM policies, practices and interventions that can contribute to environmental management.